ASUHAN KEPERAWATAN ANAK PADA AN. A DENGAN DBD TERHADAP PENERAPAN SARI KURMA DI RUANG ANYELIR RUMAH SAKIT EMBUNG FATIMAH KOTA BATAM TAHUN 2021 - Trisya Yona Febrina; Ditte Ayu Suntara; Afif D Alba (Jurnal Inovasi Penelitian, 2022)
BACKGROUND: Dengue hemorrhagic fever was first recognized in Southeast Asia, more precisely in the Philippines in 1953, because of cases of fever that attacked children accompanied by bleeding and shock manifestations. The number of cases of dengue hemorrhagic fever (DHF) in Indonesia experienced a drastic spike in early 2020. The Ministry of Health noted that the number of cases of DHF in Indonesia had crossed the 16,000 mark, in the period from January to early March 2020. Of that number, 100 people died. The best way to avoid dengue is to adopt a healthy lifestyle (Suiraoka, 2012). One of them is in non-pharmacological treatment, namely by giving date palm juice, the method used is safer, easier and simpler (Reni, 2018).OBJECTIVE: To apply nursing care to dengue hemorrhagic fever patients which includes assessment, diagnosis, intervention, implementation and evaluation. METHOD: The research design method used is descriptive using case studies. The respondents used were 1 pediatric patient with a medical diagnosis of Dengue Hemorrhagic Fever. RESULT: The application of nursing care in accordance with the nursing process will achieve good results in accordance with the predetermined outcome criteria. Giving nursing actions to drink date palm juice can increase the platelet value of An.A. And An. A is able to do therapy by drinking date juice independently.